Aspek Hukum dalam Transaksi Ekonomi Digital Mengungkap Tantangan Kompleks dan Solusi Masa Kini - Sisca Juliana (RETORIKA: Journal of Law, Social, and Humanities, 2023)
This study aims to: 1) Analyze the legal regulations for digital economic transactions in Indonesia to ensure legal certainty for businesses and consumers, 2) Identify the main legal challenges that arise in the practice of digital economic transactions, and 3) Formulate effective legal solutions to overcome challenges in digital economic transactions. This type of research is normative legal research with a statutory, conceptual, and analytical approach. The legal materials for this study consist of primary, secondary, and tertiary legal materials. The analysis of legal materials uses legal interpretation, legal theory, and legal principles. The results of the study indicate that the legal regulations for digital economic transactions in Indonesia are available, but legal certainty for businesses and consumers still needs to be strengthened. The main challenges include consumer protection, data security, and the compatibility of traditional legal principles with the fast and cross-platform nature of digital transactions. Legal solutions include regulatory harmonization, the application of adaptive legal principles, and the utilization of digital contract principles to ensure that rights, obligations, and transaction security are effectively protected.